Comparison of Speech Skills of 8th and 9th Grade Students with the Theme of Interfaith Tolerance at SMP Negeri 1 Tarik - Abdurrahman Hakim (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to analyze and compare the public speaking skills of eighth- and ninth-grade students at SMP Negeri 1 Tarik on the theme of interfaith tolerance. The study employed a quantitative approach with a comparative design. The study sample consisted of 30 students, comprising 15 eighth-grade students and 15 ninth-grade students. Data were collected through a speech performance test using an assessment rubric that covered aspects of content mastery, speech structure, language, delivery techniques, and time management. Data analysis was conducted descriptively and inferentially. A preliminary test indicated that the data were not fully normally distributed; therefore, the Mann–Whitney U test was used to test for differences between groups. The results of the study showed that the public speaking skills of eighth-grade students fell into the “very good” category with an average of 96.13 and a relatively homogeneous distribution of scores, while ninth-grade students fell into the “good” category with an average of 90.27 and a wider variation in scores. The results of the Mann–Whitney U test indicated a significant difference between the two groups (p < 0.05). In general, eighth-grade students demonstrated higher achievement in nearly all assessment aspects compared to ninth-grade students. These findings indicate that public speaking ability is not solely influenced by grade level but also by other factors such as the intensity of practice, mastery of the material, motivation, and students’ psychological conditions. This study underscores the importance of implementing adaptive, continuous, and process-oriented speaking learning strategies to optimally improve students’ public speaking skills.